High-temperature-resistant heat-conducting silicone rubber composite material and preparation process thereof

CN123004142APending Publication Date: 2026-10-30JIANGXI SILICON-BASED SCIENCE & TECHNOLOGY RESEARCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611314385.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但常规纯硅橡胶本身导热系数极低,在高功率器件工作时无法快速导出热量,易造成局部热量积聚引发器件失效,同时,其自身为绝缘材料,静电无法及时耗散,在特殊工况下易产生静电积聚,不仅会吸附灰尘,而且容易引发电路干扰乃至安全隐患

Benefits of technology

1、本发明中,通过将甲基苯基含氢硅油与烯丙基茴香醚在催化剂催化下发生加成反应,以将含苯甲醚结构的芳环侧链接枝到聚硅氧烷主链上,再与4-乙烯基环氧环己烷反应,将环氧基团接枝到硅氧烷侧链上,制得含有甲基苯基硅主链、芳醚官能团、环氧反应基团的改性剂,然后将改性剂分子上的环氧基团与石墨烯表面的羟基发生开环加成反应,形成稳定共价键,实现改性剂在石墨烯表面的牢固接枝,得到改性石墨烯,将其加入复合硅橡胶中后,由于接枝在石墨烯表面的长链甲基苯基聚硅氧烷,会在石墨烯片层周围形成空间位阻层,阻碍石墨烯片层间堆叠、团聚,同时能够提高石墨烯与硅橡胶基体的相容性,促使其均匀分散,而改性石墨烯均匀分散在硅橡胶基体中,可在硅橡胶内部形成贯穿性的二维导热通路,从而能够有效提高复合硅橡胶的导热性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004142A_ABST
    Figure CN123004142A_ABST
Patent Text Reader

Abstract

The present application relates to the field of organic polymer composite material, and particularly relates to a high-temperature-resistant and heat-conducting silicone rubber composite material and a preparation process thereof.A preparation process of a high-temperature-resistant and heat-conducting silicone rubber composite material, comprising the following steps: preparing modified graphene; preparing modified carbon nanotubes; preparing a high-temperature-resistant modifier; and preparing a silicone rubber composite material.The present application is prepared by the reaction of methylphenyl hydrogen-containing silicone oil and allyl anisole, and then the reaction of the product with 4-vinyl epoxy cyclohexane to obtain a modifier, which is then grafted on the surface of graphene to obtain modified graphene, which is then added into the composite silicone rubber, so as to improve the compatibility of graphene and the silicone rubber matrix, promote the uniform dispersion, and the uniform dispersion of the modified graphene in the silicone rubber matrix can form a two-dimensional heat-conducting path in the silicone rubber, so as to effectively improve the heat-conducting performance of the composite silicone rubber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic polymer composite materials, specifically to a high-temperature resistant thermally conductive silicone rubber composite material and its preparation process. Background Technology

[0002] Silicone rubber, due to its excellent weather resistance, high and low temperature adaptability, and flexibility, is widely used in electronics, electrical engineering, new energy equipment, aerospace, and high-end communications. It is a key polymer material for the encapsulation, thermal management, and insulation protection of various precision devices. However, conventional pure silicone rubber has an extremely low thermal conductivity, which makes it unable to quickly dissipate heat when high-power devices are operating. This can easily lead to localized heat accumulation and device failure. At the same time, as an insulating material, it cannot dissipate static electricity in a timely manner, and under special operating conditions, it is prone to static electricity accumulation, which not only attracts dust but also easily causes circuit interference and even safety hazards.

[0003] Currently, the common method to improve the thermal conductivity and antistatic properties of silicone rubber is to add thermally and electrically conductive fillers to the silicone rubber matrix. However, commonly used thermally and electrically conductive fillers generally have nanoscale, high aspect ratio or two-dimensional sheet structure, with large specific surface area and extremely high surface energy. The particles will spontaneously aggregate with strong intermolecular forces to form agglomerates that are difficult to disperse. Moreover, they have poor compatibility with the low surface energy and weak polarity of the silicone rubber matrix, resulting in uneven distribution of fillers in the silicone rubber and the inability to construct a continuous and interconnected thermally and electrically conductive network.

[0004] In addition, conventional silicone rubber has limited long-term high-temperature resistance, is prone to molecular chain degradation and a sharp drop in mechanical properties in hot and oxygen environments, and has poor flame retardancy. It is also prone to melting and dripping during combustion, making it difficult to adapt to complex working conditions with high temperature, flammability, and high static electricity risk.

[0005] Therefore, it is necessary to propose a high-temperature resistant thermally conductive silicone rubber composite material with flame retardant and antistatic properties and its preparation process to extend its service life. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a high-temperature resistant thermally conductive silicone rubber composite material and its preparation process.

[0007] This invention provides a preparation process for a high-temperature resistant, thermally conductive silicone rubber composite material, comprising the following steps: S1: Preparation of modified graphene S1.1: Add methylphenyl hydrosilicone oil and allyl anisole to isopropanol at a ratio of (5.8-5.9) g: 1 g: (4.4-4.5) mL, heat and stir at 55-65℃ for 30-40 min, then add Karstedt catalyst, raise the temperature to 75-85℃, and keep the temperature and stir for 3-4 h to obtain the intermediate; S1.2: Add 4-vinylepoxycyclohexane to isopropanol at a ratio of 1g:(1.9-2)mL, stir and mix evenly, then add Karstedt catalyst to obtain a mixed solution. Add the mixed solution to the above intermediate and heat and stir at 55-65℃ for 2-3h. When cooled to 40℃, add activated carbon, keep warm and stir for 2-3h for adsorption, and then remove the activated carbon by vacuum filtration and vacuum distillation to obtain the modifier. S1.3: Place two-dimensional sheet graphene in a plasma treatment instrument and treat it in an air atmosphere for 15-20 min. Then add it to anhydrous ethanol at a ratio of 1 g: (70-80) mL, and ultrasonically disperse it at 1-3℃ for 30-40 min. Then stir for 10-20 min to obtain a graphene suspension. S1.4: Add the above modifier to anhydrous ethanol at a ratio of 1g:(80-90)mL, sonicate for 10-20min to obtain a modifier solution, then add the modifier solution to the above graphene suspension while stirring, keep warm and stir at 60-70℃ for 20-24h, cool, filter under reduced pressure, wash 3-4 times with anhydrous ethanol and vacuum dry at 50-60℃ for 10-12h to obtain modified graphene; S2: Preparation of modified carbon nanotubes A precursor was prepared by reacting 2-aminobenzimidazole with salicylaldehyde. The precursor was then reacted with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to prepare a flame retardant. The flame retardant was then grafted onto the surface of carboxylated carbon nanotubes to obtain modified carbon nanotubes. S3: Preparation of high-temperature resistant modifier The high-temperature resistant modifier is obtained by reacting o-carborane and N-bromosuccinimide under the catalysis of trifluoromethanesulfonic acid, and then mixing them with palladium acetate, triphenylphosphine, potassium carbonate and vinyltrimethoxysilane. S4: Preparation of silicone rubber composite materials Vinyl silicone oil and the above-mentioned high-temperature resistant modifier were placed in a mixer and stirred evenly. Then, hydrogen-containing silicone oil with a hydrogen content of 0.75%, hydrogen-containing silicone oil with a hydrogen content of 0.12%, 1-ethynylcyclohexanol and Karstedt catalyst were added. Vacuum stirring was continued for 10-20 minutes. Then, it was mixed with the above-mentioned modified carbon nanotubes and modified graphene. After being evenly dispersed by a three-roll mill, it was hot-pressed and vulcanized at 115-125℃ and 7-8MPa for 20-30 minutes to obtain silicone rubber composite material.

[0008] Furthermore, S2 includes the following steps: S2.1: Add 2-aminobenzimidazole to anhydrous ethanol at a ratio of 1 g: (7.5-8.5) mL, stir and disperse thoroughly, then add salicylaldehyde, continue stirring for 10-20 min, then heat to reflux at 80-85℃ for 8-10 h, cool, filter under reduced pressure, wash 2-3 times with anhydrous ethanol, and dry under vacuum at 60℃ for 10-12 h to obtain the precursor; S2.2: Add the above precursor and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous ethanol at a ratio of (1.14-1.16) g: 1 g: (6.9-7.1) mL, sonicate for 10-20 min, then reflux at 80-90 °C for 10-12 h, cool, remove ethanol by rotary evaporation, wash 2-3 times alternately with anhydrous ethanol and deionized water, and vacuum dry at 60 °C for 20-24 h to obtain the flame retardant; S2.3: Add carbon nanotubes to the acidification solution at a ratio of 1g:(35-40)mL, heat and reflux at 65-75℃ for 5-6h, cool, filter, wash with deionized water until neutral, and then vacuum dry at 60℃ for 10-12h to obtain carboxylated carbon nanotubes. S2.4: Add the above carboxylated carbon nanotubes to N,N-dimethylformamide at a ratio of 1g:(90-100)mL, and ultrasonically disperse in an ice-water bath at 1-3℃ for 1-2h to obtain a carboxylated carbon nanotube dispersion. Then add the above flame retardant to N,N-dimethylformamide at a ratio of 1g:(30-40)mL, and stir thoroughly to dissolve to obtain a flame retardant solution. S2.5: Add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to the above carboxylated carbon nanotube dispersion. Under nitrogen protection, activate the mixture by stirring in an ice bath at 3-5℃ for 40-50 min. Remove the ice bath, add the above flame retardant solution, and stir the mixture in the dark for 20-24 h. After centrifugation, washing with N,N-dimethylformamide and anhydrous ethanol three times each, dry the mixture under vacuum at 60℃ for 10-12 h to obtain modified carbon nanotubes.

[0009] Furthermore, S3 includes the following steps: S3.1: Add o-carborane and N-bromosuccinimide to hexafluoroisopropanol at a ratio of 1 g: (1.3-1.4) g: (65-70) mL, sonicate for 10-20 min, then add trifluoromethanesulfonic acid, and heat and stir at 30-40 °C for 30-40 min. Then recover hexafluoroisopropanol by vacuum distillation, wash and dry at 60 °C for 10-12 h to obtain o-carborane bromide. S3.2: Add the above-mentioned o-carborane bromide, palladium acetate and triphenylphosphine to a mixed solvent according to (2.52-2.54)g: (0.08-0.12)g: 1g: (90-100)mL. After ultrasonic treatment for 8-10min, add potassium carbonate and vinyltrimethoxysilane. Under nitrogen protection, heat and stir at 80-90℃ for 20-24h. Then, obtain the high-temperature resistant modifier by vacuum distillation and vacuum filtration.

[0010] Furthermore, the mass ratio of 4-vinylepoxycyclohexane to methylphenyl hydrogen silicone oil is 1:(7.6-7.8), and the amount of activated carbon added is 6-8% of the mass of 4-vinylepoxycyclohexane.

[0011] Furthermore, the mass ratio of the modifier to the two-dimensional sheet graphene is 1:(8-10).

[0012] Furthermore, based on platinum, the amount of Karstedt catalyst in S1.1 is 4 × 10⁻⁶ of the total mass of the reaction system. -6 In step S1.2, the amount of Karstedt catalyst used is 2 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%.

[0013] Furthermore, the molar ratio of salicylaldehyde to 2-aminobenzimidazole is 1:(0.98-1.02), the mass ratio of carboxylated carbon nanotubes, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(0.5-1):(0.3-0.6), and the mass ratio of flame retardant to carboxylated carbon nanotubes is (0.5-0.6):1.

[0014] Furthermore, the amount of trifluoromethanesulfonic acid added is 0.4-0.5% of the mass of hexafluoroisopropanol, the mass ratio of potassium carbonate to o-carborane bromide is 1:(2.6-2.7), the mass ratio of vinyltrimethoxysilane to o-carborane bromide is (1.3-1.4):1, and the mixed solvent is prepared by compounding xylene, ethanol and deionized water in a volume ratio of 3:1:1.

[0015] Furthermore, by mass percentage, the raw material composition of the silicone rubber composite material is as follows: 4.5-5.5% high-temperature resistant modifier, 0.08-0.12% hydrogen-containing silicone oil with a hydrogen content of 0.75%, 0.09-0.11% hydrogen-containing silicone oil with a hydrogen content of 0.12%, 0.013-0.027% 1-ethynylcyclohexanol, 6-8% modified carbon nanotubes, 1.5-1.9% modified graphene, 0.01-0.014% Karstedt catalyst, and the balance being vinyl silicone oil, wherein the mass fraction of platinum in the Karstedt catalyst is 3%.

[0016] A high-temperature resistant thermally conductive silicone rubber composite material, which is prepared by the preparation process of a high-temperature resistant thermally conductive silicone rubber composite material as described in any one of the above claims.

[0017] The present invention has the following advantages: 1. In this invention, a modifier containing a methylphenyl-containing silicone oil, an allyl anisole, and a methylphenyl-containing silicone oil undergo an addition reaction under catalysis to graft an aromatic ring side chain containing anisole structure onto the polysiloxane backbone. This is followed by a reaction with 4-vinylepoxycyclohexane to graft epoxy groups onto the siloxane side chain, resulting in a modifier containing a methylphenyl-containing silicone backbone, an aromatic ether functional group, and an epoxy reactive group. Then, the epoxy groups on the modifier molecule undergo a ring-opening addition reaction with the hydroxyl groups on the graphene surface to form stable covalent bonds, thus achieving the modification of the modifier in… The strong grafting of graphene onto the surface yields modified graphene. When this modified graphene is added to composite silicone rubber, the long-chain methylphenyl polysiloxane grafted onto the graphene surface forms a steric hindrance layer around the graphene sheets, preventing the stacking and aggregation of graphene sheets. At the same time, it can improve the compatibility between graphene and the silicone rubber matrix, promoting their uniform dispersion. The modified graphene, uniformly dispersed in the silicone rubber matrix, can form a penetrating two-dimensional thermal conductive path inside the silicone rubber, thereby effectively improving the thermal conductivity of the composite silicone rubber.

[0018] 2. In this invention, a Schiff base precursor is generated by undergoing a nucleophilic addition-dehydration condensation reaction between 2-aminobenzimidazole and salicylaldehyde. This precursor then undergoes a nucleophilic addition reaction with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to form a stable PC covalent bond, yielding a flame retardant with a phosphorus-nitrogen synergistic flame retardant structure. The active groups on the flame retardant molecule are then reacted with carboxyl groups on the surface of carboxylated carbon nanotubes to graft the flame retardant onto the carbon nanotube surface, resulting in modified carbon nanotubes. When these modified carbon nanotubes are added to composite silicone rubber, the grafted flame retardant macromolecules form a steric hindrance layer on the carbon nanotube surface, allowing for uniform dispersion within the silicone rubber matrix. This uniform dispersion of the modified carbon nanotubes, combined with… Uniformly dispersed modified carbon nanotubes can form a synergistic three-dimensional thermally conductive network of one-dimensional carbon nanotubes and two-dimensional graphene, significantly reducing the obstruction of heat flow transfer paths and thus synergistically improving the thermal conductivity of composite silicone rubber. At the same time, the flame retardant of the phosphorus-nitrogen synergistic flame retardant structure grafted on the surface of modified carbon nanotubes can catalyze the rapid dehydration of the silicone rubber matrix into carbon at high temperatures, forming a dense carbon layer and releasing inert gas to inhibit combustion, thereby improving the flame retardant performance of silicone rubber composites. In addition, the modified carbon nanotubes interpenetrate and overlap between modified graphene sheets, filling the interlayer pores of graphene, opening up discontinuous conductive pathways, and jointly forming a three-dimensional continuous conductive network, enabling rapid conduction of static charge, thereby synergistically improving the antistatic properties of composite silicone rubber.

[0019] 3. In this invention, under catalytic activation, N-bromosuccinimide is used as the bromine source to undergo an electrophilic substitution reaction with o-carborane. Then, palladium acetate is used as the active catalyst, triphenylphosphine as the ligand, and potassium carbonate as the acid-binding agent to react with vinyltrimethoxysilane, covalently grafting vinyltrimethoxysilane onto the o-carborane cage structure to obtain a high-temperature resistant modifier. When added to composite silicone rubber, due to the closed cage-like rigid structure of o-carborane, the intramolecular bond energy is much higher than the main chain bond energy of silicone rubber, resulting in improved high-temperature performance. The ortho-carborane cage structure does not break easily and can be embedded in the silicone rubber matrix as a heat-resistant rigid unit, inhibiting the thermal motion and unfastening degradation of the silicone rubber molecular chain, and delaying the thermal weight loss of the material. At the same time, the vinyl group in the high-temperature modifier can participate in the vulcanization reaction of silicone rubber and form covalent bonds with the silicone rubber matrix. The trimethoxysiloxane group can form Si-O-Si covalent bonds with the silicone rubber matrix, so that the carborane unit is firmly fixed in the silicone rubber crosslinking network and is not easy to precipitate at high temperature, thereby improving the long-term high-temperature resistance of the composite silicone rubber. Attached Figure Description

[0020] Figure 1 This is a flowchart illustrating the preparation process of the high-temperature resistant thermally conductive silicone rubber composite material used in an embodiment of the present invention. Detailed Implementation

[0021] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this invention.

[0022] Example 1: A preparation process for a high-temperature resistant, thermally conductive silicone rubber composite material, such as... Figure 1 As shown, it includes the following steps: S1: Preparation of modified graphene S1.1: Methylphenyl hydrosilicone oil and allyl anisole were added to isopropanol at a ratio of 5.8 g: 1 g: 4.4 mL. The mixture was heated and stirred at 55 °C for 30 min. Then, Karstedt catalyst was added, the temperature was raised to 75 °C, and the reaction was maintained at this temperature with stirring for 3 h to obtain the intermediate. The amount of Karstedt catalyst, calculated as platinum, was 4 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.2: 4-Vinylepoxycyclohexane was added to isopropanol at a ratio of 1 g: 1.9 mL. After thorough mixing, Karstedt catalyst was added to obtain a mixed solution. This mixed solution was then added to the above intermediate, and the mixture was heated and stirred at 55°C for 2 hours. After cooling to 40°C, activated carbon was added, and the mixture was kept warm and stirred for 2 hours for adsorption. The activated carbon was then removed by vacuum filtration and vacuum distillation to obtain the modifier. The mass ratio of 4-vinylepoxycyclohexane to methylphenyl hydrosilicone oil was 1:7.6, the amount of activated carbon added was 6% of the mass of 4-vinylepoxycyclohexane, and the amount of Karstedt catalyst (calculated as platinum) was 2 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.3: Place two-dimensional sheet graphene in a plasma treatment instrument and treat it in an air atmosphere for 15 min. Then add it to anhydrous ethanol at a ratio of 1 g: 70 mL, and ultrasonically disperse it at 1 °C for 30 min. Then stir for 10 min to obtain a graphene suspension. S1.4: The above modifier was added to anhydrous ethanol at a ratio of 1g:80mL, and ultrasonically treated for 10min to obtain a modifier solution. Then, while stirring, the modifier solution was added to the above graphene suspension, and the reaction was carried out at 60℃ with stirring for 20h. After cooling, the modified graphene was obtained by vacuum filtration, washing three times with anhydrous ethanol, and vacuum drying at 50℃ for 10h. The mass ratio of the modifier to the two-dimensional sheet graphene was 1:8. S2: Preparation of modified carbon nanotubes S2.1: 2-Aminobenzimidazole was added to anhydrous ethanol at a ratio of 1 g: 7.5 mL. After thorough dispersion by stirring, salicylaldehyde was added, and stirring was continued for 10 min. The mixture was then heated to reflux at 80 °C for 8 h. After cooling, the mixture was filtered under reduced pressure, washed twice with anhydrous ethanol, and dried under vacuum at 60 °C for 10 h to obtain the precursor. The molar ratio of salicylaldehyde to 2-aminobenzimidazole was 1:0.98. S2.2: The above precursor and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to anhydrous ethanol at a ratio of 1.14g:1g:6.9mL, ultrasonicated for 10min, and then heated to reflux at 80℃ for 10h. After cooling, the ethanol was removed by rotary evaporation, and then washed twice with anhydrous ethanol and deionized water alternately, and vacuum dried at 60℃ for 20h to obtain the flame retardant. S2.3: Add carbon nanotubes to the acidification solution at a ratio of 1g:35mL, heat and reflux at 65℃ for 5h, cool, filter, wash with deionized water until neutral, and then vacuum dry at 60℃ for 10h to obtain carboxylated carbon nanotubes. S2.4: Add the above carboxylated carbon nanotubes to N,N-dimethylformamide at a ratio of 1g:90mL, and ultrasonically disperse in an ice-water bath at 1℃ for 1h to obtain a carboxylated carbon nanotube dispersion. Then add the above flame retardant to N,N-dimethylformamide at a ratio of 1g:30mL, and stir thoroughly to dissolve to obtain a flame retardant solution. S2.5: 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added to the above carboxylated carbon nanotube dispersion. Under nitrogen protection, the mixture was activated by stirring in an ice bath at 3°C ​​for 40 min. After removing the ice bath, the above flame retardant solution was added, and the mixture was stirred and reacted in the dark for 20 h. After centrifugation, washing with N,N-dimethylformamide and anhydrous ethanol three times each, the mixture was dried under vacuum at 60°C for 10 h to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide was 1:0.5:0.3, and the mass ratio of flame retardant to carboxylated carbon nanotubes was 0.5:1. S3: Preparation of high-temperature resistant modifier S3.1: Add o-carborane and N-bromosuccinimide to hexafluoroisopropanol at a ratio of 1g:1.3g:65mL, sonicate for 10min, then add trifluoromethanesulfonic acid, heat and stir at 30℃ for 30min, then recover hexafluoroisopropanol by vacuum distillation, wash and dry at 60℃ for 10h to obtain o-carborane bromide, wherein the amount of trifluoromethanesulfonic acid added is 0.4% of the mass of hexafluoroisopropanol; S3.2: The above-mentioned o-carborane bromide, palladium acetate, and triphenylphosphine were added to a mixed solvent at a ratio of 2.52g:0.08g:1g:90mL. After ultrasonic treatment for 8 min, potassium carbonate and vinyltrimethoxysilane were added. The mixture was heated and stirred at 80℃ for 20 h under nitrogen protection. After vacuum distillation and vacuum filtration, a high-temperature resistant modifier was obtained. The mass ratio of potassium carbonate to o-carborane bromide was 1:2.6, and the mass ratio of vinyltrimethoxysilane to o-carborane bromide was 1.3:1. The mixed solvent was prepared by compounding xylene, ethanol, and deionized water in a volume ratio of 3:1:1. S4: Preparation of silicone rubber composite materials Vinyl silicone oil and the above-mentioned high-temperature resistant modifier were placed in a mixer and stirred evenly. Then, hydrogen-containing silicone oil with a hydrogen content of 0.75%, hydrogen-containing silicone oil with a hydrogen content of 0.12%, 1-ethynylcyclohexanol, and Karstedt catalyst were added, and vacuum stirring was continued for 10 minutes. Then, it was mixed with the above-mentioned modified carbon nanotubes and modified graphene, and dispersed evenly by a three-roll mill. After that, it was hot-pressed and vulcanized at 115°C and 7MPa for 20 minutes to obtain a silicone rubber composite material. In the above, by mass percentage, the raw material composition of the silicone rubber composite material is as follows: 4.5% high-temperature resistant modifier, 0.08% hydrogen-containing silicone oil with a hydrogen content of 0.75%, 0.09% hydrogen-containing silicone oil with a hydrogen content of 0.12%, 0.013% 1-ethynylcyclohexanol, 6% modified carbon nanotubes, 1.5% modified graphene, 0.01% Karstedt catalyst, and the balance is vinyl silicone oil. Among them, the mass fraction of platinum in the Karstedt catalyst is 3%.

[0023] Example 2: A preparation process for a high-temperature resistant, thermally conductive silicone rubber composite material, as follows: Figure 1 As shown, it includes the following steps: S1: Preparation of modified graphene S1.1: Methylphenyl hydrosilicone oil and allyl anisole were added to isopropanol in a ratio of 5.85 g: 1 g: 4.45 mL. The mixture was heated and stirred at 60 °C for 35 min. Then, Karstedt catalyst was added, the temperature was raised to 80 °C, and the reaction was maintained at this temperature with stirring for 3.5 h to obtain the intermediate. The amount of Karstedt catalyst, calculated as platinum, was 4 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.2: 4-Vinylepoxycyclohexane was added to isopropanol at a ratio of 1 g: 1.95 mL. After thorough mixing, Karstedt catalyst was added to obtain a mixed solution. This mixed solution was then added to the above intermediate, and the mixture was heated and stirred at 60°C for 2.5 h. After cooling to 40°C, activated carbon was added, and the mixture was kept warm and stirred for adsorption for 2.5 h. The activated carbon was then removed by vacuum filtration and vacuum distillation to obtain the modifier. The mass ratio of 4-vinylepoxycyclohexane to methylphenyl hydrosilicone oil was 1:7.7, the amount of activated carbon added was 7% of the mass of 4-vinylepoxycyclohexane, and the amount of Karstedt catalyst (calculated as platinum) was 2 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.3: Two-dimensional sheet graphene was placed in a plasma treatment instrument and treated in air for 17.5 min. Then it was added to anhydrous ethanol at a ratio of 1 g: 75 mL, ultrasonically dispersed at 2 °C for 35 min, and stirred for 15 min to obtain a graphene suspension. S1.4: The above modifier was added to anhydrous ethanol at a ratio of 1g:85mL, and ultrasonically treated for 15min to obtain a modifier solution. Then, while stirring, the modifier solution was added to the above graphene suspension, and the reaction was carried out at 65℃ with stirring for 22h. After cooling, the modified graphene was obtained by vacuum filtration, washing three times with anhydrous ethanol, and vacuum drying at 55℃ for 11h. The mass ratio of the modifier to the two-dimensional sheet graphene was 1:9. S2: Preparation of modified carbon nanotubes S2.1: 2-Aminobenzimidazole was added to anhydrous ethanol at a ratio of 1 g: 8 mL. After thorough dispersion by stirring, salicylaldehyde was added, and stirring was continued for 15 min. The mixture was then heated under reflux at 82.5 °C for 9 h. After cooling, the mixture was filtered under reduced pressure, washed twice with anhydrous ethanol, and dried under vacuum at 60 °C for 11 h to obtain the precursor. The molar ratio of salicylaldehyde to 2-aminobenzimidazole was 1:1. S2.2: The above precursor and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to anhydrous ethanol at a ratio of 1.15g:1g:7mL, ultrasonicated for 15min, and then heated under reflux at 85℃ for 11h. After cooling, the ethanol was removed by rotary evaporation, and the mixture was washed twice with anhydrous ethanol and deionized water alternately, and then vacuum dried at 60℃ for 22h to obtain the flame retardant. S2.3: Add carbon nanotubes to the acidification solution at a ratio of 1g:37.5mL, heat and reflux at 70℃ for 5.5h, cool, filter, wash with deionized water until neutral, and then vacuum dry at 60℃ for 11h to obtain carboxylated carbon nanotubes. S2.4: Add the above carboxylated carbon nanotubes to N,N-dimethylformamide at a ratio of 1g:95mL, and ultrasonically disperse in an ice-water bath at 2℃ for 1.5h to obtain a carboxylated carbon nanotube dispersion. Then add the above flame retardant to N,N-dimethylformamide at a ratio of 1g:35mL, and stir thoroughly to dissolve to obtain a flame retardant solution. S2.5: 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added to the above carboxylated carbon nanotube dispersion. Under nitrogen protection, the mixture was activated by stirring in an ice bath at 4°C for 45 min. After removing the ice bath, the above flame retardant solution was added, and the mixture was stirred and reacted in the dark for 22 h. After centrifugation, washing with N,N-dimethylformamide and anhydrous ethanol three times each, the mixture was dried under vacuum at 60°C for 11 h to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide was 1:0.75:0.45, and the mass ratio of flame retardant to carboxylated carbon nanotubes was 0.55:1. S3: Preparation of high-temperature resistant modifier S3.1: Add o-carborane and N-bromosuccinimide to hexafluoroisopropanol at a ratio of 1g:1.35g:67.5mL, sonicate for 15min, then add trifluoromethanesulfonic acid, heat and stir at 35℃ for 35min, then recover hexafluoroisopropanol by vacuum distillation, wash and dry at 60℃ for 11h to obtain o-carborane bromide, wherein the amount of trifluoromethanesulfonic acid added is 0.45% of the mass of hexafluoroisopropanol; S3.2: The above-mentioned o-carborane bromide, palladium acetate, and triphenylphosphine were added to a mixed solvent at a ratio of 2.53g:0.1g:1g:95mL. After ultrasonic treatment for 9 minutes, potassium carbonate and vinyltrimethoxysilane were added. The mixture was heated and stirred at 85°C for 22 hours under nitrogen protection. After vacuum distillation and vacuum filtration, a high-temperature resistant modifier was obtained. The mass ratio of potassium carbonate to o-carborane bromide was 1:2.65, and the mass ratio of vinyltrimethoxysilane to o-carborane bromide was 1.35:1. The mixed solvent was prepared by compounding xylene, ethanol, and deionized water in a volume ratio of 3:1:1. S4: Preparation of silicone rubber composite materials Vinyl silicone oil and the above-mentioned high-temperature resistant modifier were placed in a mixer and stirred evenly. Then, hydrogen-containing silicone oil with a hydrogen content of 0.75%, hydrogen-containing silicone oil with a hydrogen content of 0.12%, 1-ethynylcyclohexanol, and Karstedt catalyst were added, and vacuum stirring was continued for 15 minutes. Then, it was mixed with the above-mentioned modified carbon nanotubes and modified graphene, and dispersed evenly by a three-roll mill. After that, it was hot-pressed and vulcanized at 120°C and 7.5 MPa for 25 minutes to obtain silicone rubber composite material. The raw materials of the silicone rubber composite material, by mass percentage, are: 5% high-temperature resistant modifier, 0.1% hydrogen-containing silicone oil with a hydrogen content of 0.75%, 0.1% hydrogen-containing silicone oil with a hydrogen content of 0.12%, 0.02% 1-ethynylcyclohexanol, 7% modified carbon nanotubes, 1.7% modified graphene, 0.012% Karstedt catalyst, and the balance being vinyl silicone oil. Among them, the mass fraction of platinum in the Karstedt catalyst is 3%.

[0024] Example 3: A preparation process for a high-temperature resistant, thermally conductive silicone rubber composite material, as follows: Figure 1 As shown, it includes the following steps: S1: Preparation of modified graphene S1.1: Methylphenyl hydrosilicone oil and allyl anisole were added to isopropanol at a ratio of 5.9 g: 1 g: 4.5 mL. The mixture was heated and stirred at 65 °C for 40 min. Then, Karstedt catalyst was added, the temperature was raised to 85 °C, and the reaction was maintained at this temperature with stirring for 4 h to obtain the intermediate. The amount of Karstedt catalyst, calculated as platinum, was 4 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.2: 4-Vinylepoxycyclohexane was added to isopropanol at a ratio of 1 g: 2 mL. After mixing thoroughly, Karstedt catalyst was added to obtain a mixed solution. This mixed solution was then added to the above intermediate, and the mixture was heated and stirred at 65°C for 3 hours. After cooling to 40°C, activated carbon was added, and the mixture was kept warm and stirred for 3 hours for adsorption. The activated carbon was then removed by vacuum filtration and vacuum distillation to obtain the modifier. The mass ratio of 4-vinylepoxycyclohexane to methylphenyl hydrosilicone oil was 1:7.8, the amount of activated carbon added was 8% of the mass of 4-vinylepoxycyclohexane, and the amount of Karstedt catalyst (calculated as platinum) was 2 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%; S1.3: Two-dimensional sheet graphene was placed in a plasma treatment instrument and treated in air for 20 min. Then it was added to anhydrous ethanol at a ratio of 1 g: 80 mL, ultrasonically dispersed at 3 °C for 40 min, and stirred for 20 min to obtain a graphene suspension. S1.4: The above modifier was added to anhydrous ethanol at a ratio of 1g:90mL, and ultrasonically treated for 20min to obtain a modifier solution. Then, while stirring, the modifier solution was added to the above graphene suspension, and the reaction was carried out at 70℃ with stirring for 24h. After cooling, the modified graphene was obtained by vacuum filtration, washing 4 times with anhydrous ethanol, and vacuum drying at 60℃ for 12h. The mass ratio of modifier to two-dimensional sheet graphene was 1:10. S2: Preparation of modified carbon nanotubes S2.1: 2-Aminobenzimidazole was added to anhydrous ethanol at a ratio of 1 g: 8.5 mL. After thorough dispersion by stirring, salicylaldehyde was added, and stirring was continued for 20 min. The mixture was then heated to reflux at 85 °C for 10 h. After cooling, the mixture was filtered under reduced pressure, washed three times with anhydrous ethanol, and dried under vacuum at 60 °C for 12 h to obtain the precursor. The molar ratio of salicylaldehyde to 2-aminobenzimidazole was 1:1.02. S2.2: The above precursor and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide were added to anhydrous ethanol at a ratio of 1.16g:1g:7.1mL, ultrasonicated for 20min, and then heated under reflux at 90℃ for 12h. After cooling, the ethanol was removed by rotary evaporation, and then washed three times alternately with anhydrous ethanol and deionized water, and vacuum dried at 60℃ for 24h to obtain the flame retardant. S2.3: Add carbon nanotubes to the acidification solution at a ratio of 1g:40mL, heat and reflux at 75℃ for 6h, cool, filter, wash with deionized water until neutral, and then vacuum dry at 60℃ for 12h to obtain carboxylated carbon nanotubes. S2.4: Add the above carboxylated carbon nanotubes to N,N-dimethylformamide at a ratio of 1g:100mL, and ultrasonically disperse in an ice-water bath at 3℃ for 2h to obtain a carboxylated carbon nanotube dispersion. Then add the above flame retardant to N,N-dimethylformamide at a ratio of 1g:40mL, and stir thoroughly to dissolve to obtain a flame retardant solution. S2.5: 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide were added to the above carboxylated carbon nanotube dispersion. Under nitrogen protection, the mixture was activated by stirring in an ice bath at 5°C for 50 min. After removing the ice bath, the above flame retardant solution was added, and the mixture was stirred and reacted in the dark for 24 h. After centrifugation, washing with N,N-dimethylformamide and anhydrous ethanol three times each, the mixture was dried under vacuum at 60°C for 12 h to obtain modified carbon nanotubes. The mass ratio of carboxylated carbon nanotubes, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide was 1:1:0.6, and the mass ratio of flame retardant to carboxylated carbon nanotubes was 0.6:1. S3: Preparation of high-temperature resistant modifier S3.1: Add o-carborane and N-bromosuccinimide to hexafluoroisopropanol at a ratio of 1g:1.4g:70mL, sonicate for 20min, then add trifluoromethanesulfonic acid, heat and stir at 40℃ for 40min, then recover hexafluoroisopropanol by vacuum distillation, wash and dry at 60℃ for 12h to obtain o-carborane bromide, wherein the amount of trifluoromethanesulfonic acid added is 0.5% of the mass of hexafluoroisopropanol; S3.2: The above-mentioned o-carborane bromide, palladium acetate, and triphenylphosphine were added to a mixed solvent at a ratio of 2.54g:0.12g:1g:100mL. After ultrasonic treatment for 10min, potassium carbonate and vinyltrimethoxysilane were added. The mixture was heated and stirred at 90℃ for 24h under nitrogen protection. After vacuum distillation and vacuum filtration, a high-temperature resistant modifier was obtained. The mass ratio of potassium carbonate to o-carborane bromide was 1:2.7, and the mass ratio of vinyltrimethoxysilane to o-carborane bromide was 1.4:1. The mixed solvent was prepared by compounding xylene, ethanol, and deionized water in a volume ratio of 3:1:1. S4: Preparation of silicone rubber composite materials Vinyl silicone oil and the above-mentioned high-temperature resistant modifier were placed in a mixer and stirred evenly. Then, hydrogen-containing silicone oil with a hydrogen content of 0.75%, hydrogen-containing silicone oil with a hydrogen content of 0.12%, 1-ethynylcyclohexanol, and Karstedt catalyst were added, and vacuum stirring was continued for 20 minutes. Then, it was mixed with the above-mentioned modified carbon nanotubes and modified graphene, and dispersed evenly using a three-roll mill. Finally, it was hot-pressed and vulcanized at 125℃ and 8MPa for 30 minutes to obtain a silicone rubber composite material. The raw material composition of the silicone rubber composite material, by mass percentage, is as follows: 5.5% high-temperature resistant modifier, 0.12% hydrogen-containing silicone oil with a hydrogen content of 0.75%, 0.11% hydrogen-containing silicone oil with a hydrogen content of 0.12%, 0.027% 1-ethynylcyclohexanol, 8% modified carbon nanotubes, 1.9% modified graphene, 0.014% Karstedt catalyst, and the balance is vinyl silicone oil. Among them, the mass fraction of platinum in the Karstedt catalyst is 3%.

[0025] Comparative Example 1 differs from Example 1 in that the modified graphene in step S4 is replaced with an equal amount of two-dimensional sheet graphene, i.e., the surface of the two-dimensional sheet graphene is not modified.

[0026] Comparative Example 2 differs from Example 1 in that the modified carbon nanotubes in step S4 are replaced with an equal amount of carbon nanotubes, i.e., the carbon nanotubes are not modified.

[0027] Comparative Example 3 differs from Example 1 in that the modified carbon nanotubes in step S4 are replaced with an equal amount of modified graphene.

[0028] Comparative Example 4 differs from Example 1 in that the modified graphene in step S4 is replaced with an equal amount of modified carbon nanotubes.

[0029] Comparative Example 5 differs from Example 1 in that the modified graphene and modified carbon nanotubes in step S4 are removed.

[0030] Comparative Example 6 differs from Example 1 in that the high-temperature modifier in step S4 is removed.

[0031] Comparative Example 7 differs from Example 1 in that the high-temperature resistant modifier in step S4 is replaced with an equal amount of o-carborane.

[0032] Test example: Test 1: The silicone rubber composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were cut into 100mm×100mm×2mm samples. The thermal conductivity at 25℃ was then tested using a transient thermal conductivity tester. Each group was tested three times, and the average value was taken. The results are shown in Table 1.

[0033] Table 1: Thermal conductivity test results

[0034] As shown in Table 1, in Comparative Example 1, the thermal conductivity of the silicone rubber composite material obtained without surface modification of the two-dimensional sheet graphene was significantly lower than that in Example 1. This indicates that by reacting methylphenyl hydrogen-containing silicone oil with allyl anisole under catalyst catalysis to graft the aromatic ring side chain containing anisole structure onto the polysiloxane backbone, and then reacting it with 4-vinylepoxycyclohexane to graft epoxy groups onto the siloxane side chain, a modifier containing a methylphenyl silicon backbone, aromatic ether functional groups, and epoxy reactive groups is obtained. Then, the epoxy groups on the modifier molecule undergo a ring-opening addition reaction with the hydroxyl groups on the graphene surface to form stable covalent bonds, achieving a firm grafting of the modifier onto the graphene surface, resulting in modified graphene. Adding this modified graphene to the composite silicone rubber can improve the compatibility between graphene and the silicone rubber matrix, promoting its uniform dispersion. The uniform dispersion of modified graphene in the silicone rubber matrix can effectively improve the thermal conductivity of the composite silicone rubber.

[0035] Furthermore, in Comparative Example 2, without surface modification of carbon nanotubes, the thermal conductivity of the resulting silicone rubber composite material was higher than that of Comparative Example 5, but lower than that of Example 1. In Comparative Examples 3 and 4, when only one of modified graphene or modified carbon nanotubes was added, the thermal conductivity of the resulting silicone rubber composite material was higher than that of Comparative Examples 1, 2, and 5, but still lower than that of Example 1. This demonstrates that by undergoing a nucleophilic addition-dehydration condensation reaction between 2-aminobenzimidazole and salicylaldehyde to generate a Schiff base precursor, which is then reacted with 9,1... O-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide undergoes a nucleophilic addition reaction to form a stable PC covalent bond, yielding a flame retardant with a phosphorus-nitrogen synergistic flame retardant structure. Then, the active groups on the flame retardant molecule react with the carboxyl groups on the surface of carboxylated carbon nanotubes to graft the flame retardant onto the carbon nanotube surface, resulting in modified carbon nanotubes. After being added to composite silicone rubber, the modified carbon nanotubes are uniformly dispersed in the silicone rubber matrix. The uniformly dispersed modified carbon nanotubes synergistically improve the thermal conductivity of the composite silicone rubber.

[0036] Test 2: The silicone rubber composite materials prepared in Examples 1-3 and Comparative Example 2 were cut into 100mm×10mm×2mm samples, and their limiting oxygen index was tested using an oxygen index meter. Each group was tested three times, and the average value was taken. The results are shown in Table 2.

[0037] Table 2: Limiting Oxygen Index Test Results

[0038] As shown in Table 2, when no modification of carbon nanotubes was performed in Comparative Example 2, the limiting oxygen index of the silicone rubber composite material was lower than that in Example 1. It can be seen that the flame retardant with phosphorus-nitrogen synergistic flame retardant structure grafted on the surface of modified carbon nanotubes can catalyze the rapid dehydration of the silicone rubber matrix into carbon at high temperature, forming a dense carbon layer and releasing inert gas to inhibit combustion, thereby improving the flame retardant performance of silicone rubber.

[0039] Test 3: The silicone rubber composite materials prepared in Examples 1-3 and Comparative Examples 3-5 were cut into 100mm×100mm×2mm samples. The volume resistivity at 25℃ and RH50% was then measured using a high resistance meter. Each group was tested three times, and the average value was taken. The results are shown in Table 3.

[0040] Table 3: Volume resistivity test results

[0041] As shown in Table 3, when only one of modified graphene or modified carbon nanotubes was added in Comparative Examples 3 and 4, the volume resistivity of the silicone rubber composite material was lower than that of Comparative Example 5, but still higher than that of Example 1. This shows that modified carbon nanotubes and modified graphene sheets can synergistically improve the antistatic properties of the composite silicone rubber.

[0042] Test 4: The silicone rubber composite materials prepared in Examples 1-3 and Comparative Example 6 were cut into 3mm×3mm×2mm samples. Then, a thermogravimetric analyzer was used to heat the samples to 800℃ in a nitrogen atmosphere at a rate of 10℃ / min. The 5% thermogravimetric temperature was recorded. Each group was tested three times, and the average value was taken. The results are shown in Table 4.

[0043] Table 4: Results of 5% Thermogravimetric Temperature Test

[0044] Test 5: Referring to GB / T 528-2009, the silicone rubber composite materials prepared in Examples 1-3 and Comparative Example 7 were respectively made into Type 2 dumbbell plates with a thickness of 2 mm. Then, their initial tensile strength and tensile strength after aging in a hot air aging chamber at 250℃ for 168 h were tested, and the tensile strength retention rate was calculated using the following formula: Tensile strength retention rate = tensile strength after aging for 168 hours / initial tensile strength × 100%. Each group was tested three times, and the average value was taken. The results are shown in Table 5.

[0045] Table 5: Tensile Strength Retention Rate Test Results

[0046] As shown in Tables 4 and 5, in Comparative Example 6, without the addition of a high-temperature modifier, the 5% thermal weight loss temperature of the prepared silicone rubber composite material was lower than that of Example 1. In Comparative Example 7, with the direct physical addition of o-carborane, the tensile strength retention rate of the prepared silicone rubber composite material after 250°C heat aging for 168 hours was much lower than that of Example 1. It can be seen that by using N-bromosuccinimide as a bromine source under catalyst activation to conduct an electrophilic substitution reaction on o-carborane, and then using palladium acetate as an active catalyst, triphenylphosphine as a ligand, and potassium carbonate as an acid-binding agent to react with vinyltrimethoxysilane, vinyltrimethoxysilane is covalently grafted onto the o-carborane cage structure to obtain a high-temperature modifier. After adding it to the composite silicone rubber, it can delay the thermal weight loss and thermal aging of the material and improve the long-term high-temperature resistance of the composite silicone rubber.

[0047] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.

Claims

1. A preparation process for a high-temperature resistant, thermally conductive silicone rubber composite material, characterized in that, Includes the following steps: S1: Preparation of modified graphene S1.1: Add methylphenyl hydrosilicone oil and allyl anisole to isopropanol at a ratio of (5.8-5.9) g: 1 g: (4.4-4.5) mL, heat and stir at 55-65℃ for 30-40 min, then add Karstedt catalyst, raise the temperature to 75-85℃, and keep the temperature and stir for 3-4 h to obtain the intermediate; S1.2: Add 4-vinylepoxycyclohexane to isopropanol at a ratio of 1g:(1.9-2)mL, stir and mix evenly, then add Karstedt catalyst to obtain a mixed solution. Add the mixed solution to the above intermediate and heat and stir at 55-65℃ for 2-3h. When cooled to 40℃, add activated carbon, keep warm and stir for 2-3h for adsorption, and then remove the activated carbon by vacuum filtration and vacuum distillation to obtain the modifier. S1.3: Place two-dimensional sheet graphene in a plasma treatment instrument and treat it in an air atmosphere for 15-20 min. Then add it to anhydrous ethanol at a ratio of 1 g: (70-80) mL, and ultrasonically disperse it at 1-3℃ for 30-40 min. Then stir for 10-20 min to obtain a graphene suspension. S1.4: Add the above modifier to anhydrous ethanol at a ratio of 1g:(80-90)mL, sonicate for 10-20min to obtain a modifier solution, then add the modifier solution to the above graphene suspension while stirring, keep warm and stir at 60-70℃ for 20-24h, cool, filter under reduced pressure, wash 3-4 times with anhydrous ethanol and vacuum dry at 50-60℃ for 10-12h to obtain modified graphene; S2: Preparation of modified carbon nanotubes A precursor was prepared by reacting 2-aminobenzimidazole with salicylaldehyde. The precursor was then reacted with 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to prepare a flame retardant. The flame retardant was then grafted onto the surface of carboxylated carbon nanotubes to obtain modified carbon nanotubes. S3: Preparation of high-temperature resistant modifier The high-temperature resistant modifier is obtained by reacting o-carborane and N-bromosuccinimide under the catalysis of trifluoromethanesulfonic acid, and then mixing them with palladium acetate, triphenylphosphine, potassium carbonate and vinyltrimethoxysilane. S4: Preparation of silicone rubber composite materials Vinyl silicone oil and the above-mentioned high-temperature resistant modifier were placed in a mixer and stirred evenly. Then, hydrogen-containing silicone oil with a hydrogen content of 0.75%, hydrogen-containing silicone oil with a hydrogen content of 0.12%, 1-ethynylcyclohexanol and Karstedt catalyst were added. Vacuum stirring was continued for 10-20 minutes. Then, it was mixed with the above-mentioned modified carbon nanotubes and modified graphene. After being evenly dispersed by a three-roll mill, it was hot-pressed and vulcanized at 115-125℃ and 7-8MPa for 20-30 minutes to obtain silicone rubber composite material.

2. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 1, characterized in that, S2 includes the following steps: S2.1: Add 2-aminobenzimidazole to anhydrous ethanol at a ratio of 1 g: (7.5-8.5) mL, stir and disperse thoroughly, then add salicylaldehyde, continue stirring for 10-20 min, then heat to reflux at 80-85℃ for 8-10 h, cool, filter under reduced pressure, wash 2-3 times with anhydrous ethanol, and dry under vacuum at 60℃ for 10-12 h to obtain the precursor; S2.2: Add the above precursor and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to anhydrous ethanol at a ratio of (1.14-1.16) g: 1 g: (6.9-7.1) mL, sonicate for 10-20 min, then reflux at 80-90 °C for 10-12 h, cool, remove ethanol by rotary evaporation, wash 2-3 times alternately with anhydrous ethanol and deionized water, and vacuum dry at 60 °C for 20-24 h to obtain the flame retardant; S2.3: Add carbon nanotubes to the acidification solution at a ratio of 1g:(35-40)mL, heat and reflux at 65-75℃ for 5-6h, cool, filter, wash with deionized water until neutral, and then vacuum dry at 60℃ for 10-12h to obtain carboxylated carbon nanotubes. S2.4: Add the above carboxylated carbon nanotubes to N,N-dimethylformamide at a ratio of 1g:(90-100)mL, and ultrasonically disperse in an ice-water bath at 1-3℃ for 1-2h to obtain a carboxylated carbon nanotube dispersion. Then add the above flame retardant to N,N-dimethylformamide at a ratio of 1g:(30-40)mL, and stir thoroughly to dissolve to obtain a flame retardant solution. S2.5: Add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide to the above carboxylated carbon nanotube dispersion. Under nitrogen protection, activate the mixture by stirring in an ice bath at 3-5℃ for 40-50 min. Remove the ice bath, add the above flame retardant solution, and react with stirring in the dark for 20-24 h. After centrifugation, washing with N,N-dimethylformamide and anhydrous ethanol three times each, dry the mixture under vacuum at 60℃ for 10-12 h to obtain modified carbon nanotubes.

3. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 2, characterized in that, S3 includes the following steps: S3.1: Add o-carborane and N-bromosuccinimide to hexafluoroisopropanol at a ratio of 1 g: (1.3-1.4) g: (65-70) mL, sonicate for 10-20 min, then add trifluoromethanesulfonic acid, and heat and stir at 30-40 °C for 30-40 min. Then recover hexafluoroisopropanol by vacuum distillation, wash and dry at 60 °C for 10-12 h to obtain o-carborane bromide. S3.2: Add the above-mentioned o-carborane bromide, palladium acetate and triphenylphosphine to a mixed solvent according to (2.52-2.54)g: (0.08-0.12)g: 1g: (90-100)mL. After ultrasonic treatment for 8-10min, add potassium carbonate and vinyltrimethoxysilane. Under nitrogen protection, heat and stir at 80-90℃ for 20-24h. Then, obtain the high-temperature resistant modifier by vacuum distillation and vacuum filtration.

4. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 1, characterized in that, The mass ratio of 4-vinylepoxycyclohexane to methylphenyl hydrogen-containing silicone oil is 1:(7.6-7.8), and the amount of activated carbon added is 6-8% of the mass of 4-vinylepoxycyclohexane.

5. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 1, characterized in that, The mass ratio of the modifier to the two-dimensional sheet graphene is 1:(8-10).

6. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 1, characterized in that, Based on platinum, the amount of Karstedt catalyst in S1.1 is 4 × 10⁻⁶ of the total mass of the reaction system. -6 In step S1.2, the amount of Karstedt catalyst used is 2 × 10⁻⁶ of the total mass of the reaction system. -6 Furthermore, the mass fraction of platinum in the Karstedt catalyst is 3%.

7. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 2, characterized in that, The molar ratio of salicylaldehyde to 2-aminobenzimidazole is 1:(0.98-1.02), the mass ratio of carboxylated carbon nanotubes, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide is 1:(0.5-1):(0.3-0.6), and the mass ratio of flame retardant to carboxylated carbon nanotubes is (0.5-0.6):

1.

8. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 3, characterized in that, The amount of trifluoromethanesulfonic acid added is 0.4-0.5% of the mass of hexafluoroisopropanol. The mass ratio of potassium carbonate to o-carborane bromide is 1:(2.6-2.7), and the mass ratio of vinyltrimethoxysilane to o-carborane bromide is (1.3-1.4):

1. The mixed solvent is prepared by compounding xylene, ethanol and deionized water in a volume ratio of 3:1:

1.

9. The preparation process of a high-temperature resistant thermally conductive silicone rubber composite material according to claim 1, characterized in that, The raw material composition of the silicone rubber composite material, by mass percentage, is as follows: 4.5-5.5% high-temperature resistant modifier, 0.08-0.12% hydrogen-containing silicone oil with a hydrogen content of 0.75%, 0.09-0.11% hydrogen-containing silicone oil with a hydrogen content of 0.12%, 0.013-0.027% 1-ethynylcyclohexanol, 6-8% modified carbon nanotubes, 1.5-1.9% modified graphene, 0.01-0.014% Karstedt catalyst, and the balance being vinyl silicone oil. Among them, the mass fraction of platinum in the Karstedt catalyst is 3%.

10. A high-temperature resistant, thermally conductive silicone rubber composite material, characterized in that, It is prepared by the preparation process of a high-temperature resistant thermally conductive silicone rubber composite material as described in any one of claims 1-9.